Hepatitis--Bs antigen in an isolated Indian population of southern Venezuela: a family study. - Soyano, A (1979)
A genetic analysis of the presence of HBsAg in a population of which 7.2% of the members were positive is presented. Though the ratios of carriers: non-carriers were generally in good agreement with expectation if the carrier state were determined by homozygosity for a single recessive gene, the two examples of mating most critical to a test of the hypothesis, carrier X carrier, yielded 2 normal children among 4 in one family, and one normal child, the only offspring, in the second family. Other investigators have reported similar findings. We conclude that the hypothesis of simple recessive inheritance cannot be sustained.